PENERAPAN MODEL PROBLEM BASED LEARNING DENGAN MEDIA WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR SISWA TENTANG SIKLUS AIR PADA MATA PELAJARAN IPA DI KELAS V SD NEGERI 3 PANGURAGAN WETAN - Khayatun Nufus; Nurkholis; Nur Asyah (STKIP Subang, 2023)
The purpose of this study was to find out and describe the steps for implementing PBL in improving science learning outcomes with material on the water cycle process at SD Negeri 3 Panguragan Wetam in class V which had not yet reached (KKM). This type of research is classroom action research (PTK) carried out in 2 cycles. Collecting information using test and non-test techniques, data were analyzed using descriptive techniques. The research subjects were class V SD Negeri 3 Panguragan Wetan totaling 34 students. The results showed that cognitive learning outcomes from pre-cycle 15 students (45%) increased to 26 students (77%) in cycle II increased to 34 students (100%) in cycle III. Affective learning outcomes in cycle II and cycle III showed an average politeness of 87 increased to 98, caring 76 to 83 and responsibility 84 to 93. Psychomotor learning in cycles II and III averaged aspects of practical skills 89 to 96, accuracy 77 to 84, representing 75 to 87. It can be concluded that the application of the problem based learning (PBL) model can improve learning outcomes in the water cycle material both from cognitive, affective and psychomotor.